Organ dysfunction, injury and failure in acute heart failure: from pathophysiology to diagnosis and management. A review on behalf of the Acute Heart Failure Committee of the Heart Failure Association (HFA) of the European Society of Cardiology (ESC) - Harjola, Veli‐Pekka; Mullens, Wilfried; Banaszewski, Marek; Bauersachs, Johann; Brunner‐La Rocca, Hans‐Peter; Chioncel, Ovidiu; Collins, Sean P.; Doehner, Wolfram; Filippatos, Gerasimos S.; Flammer, Andreas J.; Fuhrmann, Valentin; Lainscak, Mitja; et al. (European journal of heart failure, 2017)
Organ injury and impairment are commonly observed in patients with acute heart failure (AHF), and congestion is an essential pathophysiological mechanism of impaired organ function. Congestion is the predominant clinical profile in most patients with AHF; a smaller proportion presents with peripheral hypoperfusion or cardiogenic shock. Hypoperfusion further deteriorates organ function. The injury and dysfunction of target organs (i.e. heart, lungs, kidneys, liver, intestine, brain) in the setting of AHF are associated with increased risk for mortality. Improvement in organ function after decongestive therapies has been associated with a lower risk for post‐discharge mortality. Thus, the prevention and correction of organ dysfunction represent a therapeutic target of interest in AHF and should be evaluated in clinical trials. Treatment strategies that specifically prevent, reduce or reverse organ dysfunction remain to be identified and evaluated to determine if such interventions impact mortality, morbidity and patient‐centred outcomes. This paper reflects current understanding among experts of the presentation and management of organ impairment in AHF and suggests priorities for future research to advance the field.